2010
DOI: 10.1016/j.jvs.2009.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Renal parenchymal preservation after percutaneous renal angioplasty and stenting

Abstract: While parenchymal preservation occurs in most patients, parenchymal loss occurs in 31% of patients and is associated with markers of impaired parenchymal perfusion (resistive index and nephrosclerosis grade) at the time of intervention. Pre-existing renal size or volumes were not predictive of parenchymal loss. Parenchymal loss is associated with a significant decrease in survival and a marked increased renal related morbidity and progression to hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition, Bommart et al used different criteria to define BP response than we used in the current study, which could also account for the discrepancies between the two studies. In the current study, we focused on preoperative renal volume as a predictor of outcome, but postoperative renal volume also has prognos- 11 found that patients who suffered parenchymal volume loss after RAS had worse long-term survival and higher rates of progression to dialysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Bommart et al used different criteria to define BP response than we used in the current study, which could also account for the discrepancies between the two studies. In the current study, we focused on preoperative renal volume as a predictor of outcome, but postoperative renal volume also has prognos- 11 found that patients who suffered parenchymal volume loss after RAS had worse long-term survival and higher rates of progression to dialysis.…”
Section: Discussionmentioning
confidence: 96%
“…The estimated renal volume was calculated from these measurements: kidney length ϫ width ϫ (depth/ 2). 10,11 All measurements were performed in duplicate and averaged for each stented kidney.…”
Section: Study Population and Clinical Data Collectionmentioning
confidence: 99%
“…A study done by Davies et al analyzed renal parenchymal preservation and that patients who had parenchymal losses were found to have higher RRI. This was correlated with worse clinical outcomes and faster progression to dialysis [14]. Zeller et al divided 176 patients into three groups based on RRI (RI < 0.7, RI 0.7-0.8, RI > 0.8), and it was found that the improvement in renal function and the reduction in BP were the same across all study groups [15].…”
Section: Discussionmentioning
confidence: 99%
“…This technique for assessing kidney volume was previously validated in an autopsy study 10 and used in prior studies. 6,11 Increased kidney volume was defined as an increase of Ն5% over baseline, whereas decreased kidney volume required a decline in kidney volume by Ն5%. Stable kidney volume was defined by any change in kidney volume of Ͻ5% over baseline.…”
Section: This Study Was Approved By the Institutional Reviewmentioning
confidence: 99%